2011
DOI: 10.1111/j.1399-3062.2011.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for late‐onset cytomegalovirus disease in donor seropositive/recipient seronegative kidney transplant recipients who receive antiviral prophylaxis

Abstract: Background Cytomegalovirus (CMV) disease occurs frequently after cessation of antiviral prophylaxis in CMV-seronegative kidney transplant recipients from seropositive donors (D+ R−), and the risk factors are incompletely defined. Methods We retrospectively assessed the incidence, clinical features, and risk factors for CMV disease in a cohort of D+ R− kidney transplant recipients who received antiviral prophylaxis at a single US transplant center using descriptive statistics and Cox proportional hazards mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 15 publications
1
27
2
Order By: Relevance
“…In another series of D+/R− kidney recipients, 51 patients (29%) developed CMV disease at a median of 61 days (interquartile range, 40-143 days) after stopping 3 months of antiviral prophylaxis (19). In a third series of D+/R− renal transplant recipients on 3 to 6 months of antiviral prophylaxis, CMV disease developed in 29 of 113 (26%) at a median of 185 days posttransplant (range 116-231 days), including CMV syndrome (66%) and tissue invasive disease (34%) (20). All series have a relatively high rate of late CMV, underscoring the ability of preventative antiviral therapy to delay but not prevent CMV infection.…”
Section: Universal Prophylaxis and Preemptive Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…In another series of D+/R− kidney recipients, 51 patients (29%) developed CMV disease at a median of 61 days (interquartile range, 40-143 days) after stopping 3 months of antiviral prophylaxis (19). In a third series of D+/R− renal transplant recipients on 3 to 6 months of antiviral prophylaxis, CMV disease developed in 29 of 113 (26%) at a median of 185 days posttransplant (range 116-231 days), including CMV syndrome (66%) and tissue invasive disease (34%) (20). All series have a relatively high rate of late CMV, underscoring the ability of preventative antiviral therapy to delay but not prevent CMV infection.…”
Section: Universal Prophylaxis and Preemptive Therapymentioning
confidence: 99%
“…A metaanalysis of 11 randomized trials (698 patients; median follow-up: 12 months, range: 3-22 months), with six randomized trials (302 patients) after kidney transplantation, demonstrated a beneficial effect of the prophylactic use of CMV immunoglobulin on total survival and prevention of Should not be used 1500 mg once a day, or 500 mg three times a day Should not be used 1000 mg once a day, or 500 mg twice a day [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Should not be used 500 mg once a day <10…”
Section: Antiviral Medications For Universal Prophylaxis and Preemptimentioning
confidence: 99%
“…However, sensitive DNA-based techniques commonly detect CMV persistence after transplantation in kidneys from seropositive donors, 24 suggesting that donor tissue may act as a "reservoir" for infection, which may later become clinically manifest. 25 Certainly the preimplantation histologic data from the current study suggest peri-transplantation CMV transmission is very common. After CMV reactivation, HLA class I upregulation occurs in infected and surrounding cells, [26][27][28][29] with subsequent presentation of CMVantigens to CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…One major disadvantage of the universal prophylaxis strategy is the development of late-onset CMV disease, disease which occurs after the discontinuation of prophylaxis. Late-onset CMV disease occurs in up to 30% of high risk D+/Rrecipients, and is associated with allograft loss and mortality [60][61][62]. This presumably occurs due the lack of development of CMV-specific cell-mediated immunity in this population.…”
Section: Prevention Of Gastrointestinal Tract CMV Infectionmentioning
confidence: 98%
“…This presumably occurs due the lack of development of CMV-specific cell-mediated immunity in this population. Risk factors for late-onset CMV disease include D+/R-serostatus, higher immunosuppression, retransplantation, and graft rejection [61,63]. Prevention of late-onset CMV disease remains an area where further study is needed, follow-up data from the IMPACT study suggest that extended duration valganciclovir prophylaxis is associated with long-term reduction in CMV disease at 2 years post-transplant [64•].…”
Section: Prevention Of Gastrointestinal Tract CMV Infectionmentioning
confidence: 99%